2012
DOI: 10.1186/1748-717x-7-98
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating breath holding and image guidance in the adjuvant gastric cancer radiotherapy: a dosimetric study

Abstract: BackgroundThe respiratory related target motion and setup error will lead to a large margin in the gastric radiotherapy. The purpose of this study is to investigate the dosimetric benefit and the possibility of incorporating the breath-hold (BH) technique with online image-guided radiotherapy in the adjuvant gastric cancer radiotherapy.MethodsSetup errors and target motions of 22 post-operative gastric cancer patients with surgical clips were analyzed. Clips movement was recorded using the digital fluoroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…We used a total margin of 7 mm in all directions to ensure adequate target coverage. This margin was originally derived from our previous study with the active breath hold technique [9]. Additionally, rotational errors also contributed to the uncertainties, and they were prominent in those fractions where maximum (7-8 mm) variations in the SI direction were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a total margin of 7 mm in all directions to ensure adequate target coverage. This margin was originally derived from our previous study with the active breath hold technique [9]. Additionally, rotational errors also contributed to the uncertainties, and they were prominent in those fractions where maximum (7-8 mm) variations in the SI direction were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier planning study [9] we compared dosimetric consequences of treatment delivery in free breathing and breath hold in the 75% phase of deep inspiration. Treatments delivered with breath hold and online image guidance allowed an increase in target dose from 45 Gy to 54 Gy while maintaining comparable dose distribution in critical organs However, dose delivery using breath hold requires purchasing additional equipment, such as active breathing control (ABC) devices, which can be costly and difficult to integrate with the linac.…”
Section: Introductionmentioning
confidence: 99%
“…The mean target motion for free breathing vs breathhold using ABC was 11.1 vs 2.2 mm, 1.9 vs 1.1 mm and 5.5 vs 1.7 mm in the SI, LR and AP directions, respectively. 53 A dosimetric study indicated that IMRT performed using breathhold could reduce the liver dose than IMRT with free breathing. 53 Hu et al 53 developed a passive breath-hold device and showed, in a pre-clinical study, that the diaphragm motion caused by respiration was reduced to ,3 mm, and the diaphragm position in different gating periods was reproducible.…”
Section: Breath-holdmentioning
confidence: 99%
“…53 A dosimetric study indicated that IMRT performed using breathhold could reduce the liver dose than IMRT with free breathing. 53 Hu et al 53 developed a passive breath-hold device and showed, in a pre-clinical study, that the diaphragm motion caused by respiration was reduced to ,3 mm, and the diaphragm position in different gating periods was reproducible. Another option of the breath-hold device is abdominal compression.…”
Section: Breath-holdmentioning
confidence: 99%
See 1 more Smart Citation